1990
DOI: 10.1002/bbpc.19900940331
|View full text |Cite
|
Sign up to set email alerts
|

The Microscopic Basis of Self Diffusion — Mutual Diffusion Relationships in Binary Liquid Mixtures

Abstract: The general relation between self and mutual diffusion coefficients in binary liquid mixtures is best described in terms of velocity cross‐correlation integrals fab. In analogy to the definition of the self diffusion coefficient in terms of a time integral over the velocity autocorrelation function, the fab are given as integrals over velocity cross‐correlation functions. As the latter coefficients are measures for the coupling of the diffusive motions between pairs of particles, they may be used for probing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Self-diffusion coefficients in mixtures are closely related to the mutual diffusion coefficients, that are needed for describing mass transfer . At infinite dilution, the self-diffusion coefficient of the infinitely diluted component in a mixture is identical with the mutual diffusion coefficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-diffusion coefficients in mixtures are closely related to the mutual diffusion coefficients, that are needed for describing mass transfer . At infinite dilution, the self-diffusion coefficient of the infinitely diluted component in a mixture is identical with the mutual diffusion coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…4−8 Self-diffusion coefficients in mixtures are closely related to the mutual diffusion coefficients, that are needed for describing mass transfer. 9 At infinite dilution, the self-diffusion coefficient of the infinitely diluted component in a mixture is identical with the mutual diffusion coefficient. Simultaneously, the selfdiffusion coefficients of the other components are not connected to the mutual diffusion coefficient at this composition.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A number of works have studied the composition dependence of velocity cross-correlations CC ij . Weingärtner observed that velocity cross-correlations CC ij show a similar composition dependence as Kirkwood–Buff coefficients G ij . However, a derivation of a relationship between velocity cross-correlations CC ij and the thermodynamic factor Γ is not straightforward and no conclusive answer was found.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…If one or more species in a liquid mixture show strong self-association, the motion of different molecules becomes strongly correlated, and this assumption breaks down. This has been formalised by the use of velocity cross-correlations (McCall and Douglass, 1967;Weingärtner, 1990). The expression for predicting mutual diffusion coefficients in such cases (i.e., mixtures in which one species is hypothesized to dimerize) was obtained by Moggridge (2012b) as:…”
Section: Introductionmentioning
confidence: 99%